Utilization of Mandarin Orange Peel Waste as an Adsorbent for Methylene Blue Dye - Muflih, Fakhri; Febrina, Laila; Mulyawati, Ira (Sustainable Environmental and Optimizing Industry Journal, 2023)
Utilization of mandarin orange peel waste as an adsorbent for methylene blue  dye is carried out to minimize methylene blue contamination. The research was conducted by using spike method samples then analyte was adsorbed. This research aims to make an adsorbent with chemical activation, which has a particle size of 100 mesh, and the quality of the adsorbent based on SNI 06-3730-199 to determine the optimum time and weight required to adsorb methylene blue. This research use Freundlich isotherm data processing and analysis of variance ANOVA. Making adsorbent is done by cleaning, then drying in an oven at a temperature of 150˚C, then put into the furnace with a temperature of 600˚C, then continued the process of testing the quality of the adsorbent based on SNI 06-3730-199. The adsorbent based on parameters contained in SNI 06-3730-1995, including 9,13% for water content, 7,26% for ash content, and 959,2 mg/g for absorption of iodine. These results have met the requirements. The optimum weight from the research is 1,5 grams, and the optimum time required for the adsorbent to absorb the analyte is 90 minutes. The efficiency of the adsorbent for absorbing methylene blue at optimum weight and interaction time is 98,93%.